A statistical approach to develop biocomposites from epoxy resin, poly(furfuryl alcohol), poly(propylene carbonate), and biochar. Issue 38 (19th June 2017) - Mashouf Roudsari, Ghodsieh; Mohanty, Amar K.; Misra, Manjusri
ABSTRACT: Epoxy composites are typically petroleum based and prone to fracture. Increasing concerns about climate change have motivated scientists to find green alternatives. To address both drawbacks, effect of addition of poly(propylene carbonate) polyol (PPC), a polyol derived from carbon dioxide, and biochar, a byproduct of pyrolysis in an epoxy/poly(furfuryl alcohol) (PFA) network was studied. It is hypothesized that addition of PPC will increase impact strength while addition of inexpensive biochar will offset cost of final product. In addition, incorporation of PFA, PPC, and biochar can increase biobased content of thermoset. A statistical approach was used to find a systematic correlation between constituent contents and mechanical properties of biocomposites. Mixture design of experiment and backward elimination regression were used to model mechanical properties of biocomposites. The fitted models showed a great ability to predict mechanical properties of new formulations. Addition of 10% biochar increased tensile strength and toughness by 13% and 34%, respectively. Biochar also increased modulus while it had adverse effect on impact strength. Promising effect of PPC on toughening of matrix was proved and it was found that addition of 30% of PPC increased impact strength by fivefolds. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45307. Abstract :